The Convex Relaxation Method on Deconvolution Model with Multiplicative Noise (Communications in Computational Physics, 2013)
In this paper, we consider variational approaches to handle the multiplicative noise removal and deblurring problem. Based on rather reasonable physicalblurring-noisy assumptions, we derive a new variational model for this issue. Afterthe study of the basic properties, we propose to approximate it by a convex relaxation model which is a balance between the previous non-convex model and a convexmodel. The relaxed model is solved by an alternating minimization approach. Numerical examples are presented to illustrate the effectiveness and efficiency of the proposedmethod.